2022
DOI: 10.1155/2022/6702773
|View full text |Cite|
|
Sign up to set email alerts
|

Thyme Oil and Thymol Counter Doxorubicin-Induced Hepatotoxicity via Modulation of Inflammation, Apoptosis, and Oxidative Stress

Abstract: Doxorubicin (DOX) is an effective anticancer agent with a wide spectrum of activities. However, it has many adverse effects on various organs especially on the liver. Thymol, one of the major components of thyme oil, has biological properties that include anti-inflammatory and antioxidant activities. Thus, this study was designed to examine thyme oil and thymol for their ability to prevent doxorubicin-induced hepatotoxicity in Wistar rats. Hepatotoxicity was induced by an intraperitoneal injection of doxorubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 92 publications
2
10
0
Order By: Relevance
“…The present investigation found that DXR-injected animals exhibited elevated levels of serum total bilirubin, which is similar with the results of Liss et al [ 70 ], Ahmed [ 71 ], Hozayen et al [ 60 ], Hassan et al [ 67 ], Ahmed et al [ 68 ], and Ahmed et al [ 72 ]. These researchers argued that it is a clear indicator of liver disease and may be caused by bile ductile occlusion induced by portal triad inflammation and fibrosis and/or conjugated bilirubin reflux from necrotic hepatocytes to sinusoids.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present investigation found that DXR-injected animals exhibited elevated levels of serum total bilirubin, which is similar with the results of Liss et al [ 70 ], Ahmed [ 71 ], Hozayen et al [ 60 ], Hassan et al [ 67 ], Ahmed et al [ 68 ], and Ahmed et al [ 72 ]. These researchers argued that it is a clear indicator of liver disease and may be caused by bile ductile occlusion induced by portal triad inflammation and fibrosis and/or conjugated bilirubin reflux from necrotic hepatocytes to sinusoids.…”
Section: Discussionsupporting
confidence: 92%
“…The damaging effects of DXR on liver cells may attributed to the stimulation of oxidative stress and inflammation. Both increased levels of LPO and TNF-α have important implications of necrosis and damage of liver cells [67][68][69] (Scheme 2). The current investigation showed that employing rutin and quercetin for the treatment of DXRinjected rats remarkably decreased the raised activities of serum ALT, AST, and ALP and the level of total bilirubin as well.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, several EOs and their components are reported to exert anti-proliferative effects and induce apoptosis in cancer cells with minimal effects on non-transformed ones [ 27 , 28 ]. Moreover, since some of them work synergistically with commonly used anticancer drugs, they have been proposed as adjuvants in chemotherapy [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…They have been recognized as sources of many bioactive products that exhibit various biological and immunological activities, including anti-inflammatory, antibacterial, antibiofilm, antifungal and antiviral effects [ 16 , 17 , 18 , 19 ]. Furthermore, EOs have been shown to exert cancer cell targeting activity to increase the efficacy of commonly used chemotherapy drugs and to possess pro-immune functions [ 20 , 21 , 22 , 23 ]. Despite a large body of research indicating that EOs and their active compounds may have anticancer properties, not many successful drug formulations have reached the clinical stage.…”
Section: Introductionmentioning
confidence: 99%
“…Zero (0) refers to the absence of lesion, “I” indicates a mild degree, “II” indicates a moderate degree, and “III” denotes a severe degree. The free software version of ImageJ (1.51d) was used for immunohistochemical examination and analysis of labeling [ 29 ]. Integrated intensities were evaluated using the ImageJ software (in pixels) for positive reactions with IL-1 β and TNF- α .…”
Section: Methodsmentioning
confidence: 99%